Influência de bundle na prevenção da infecção em sítio cirúrgico após cirurgia cardiovascular pediátrica - Marras, Ana Paula Biazi (2016)
Surgical site infection (SSI) is defined as any infection involving tissues, organs and cavities manipulated during surgical procedure. SSI occurs during the hospital admission or after discharge within 30 days after surgery. Objective: To test the hypothesis that the bundle for the prevention of SSI has influence to reduce infection after pediatric cardiovascular surgery, considering the different structural and physical situations CardioPed ICU. Patients and Methods: A total of 536 children undergoing cardiovascular surgery, 445 at Hospital de Base (HB) and 91 at Hospital da Criança e Maternidade (HCM), were retrospectively studied. The patients were divided into three groups: Group 1 (n = 230) submitted to surgical procedure at HB before bundle implementation; Group 2 (n = 215) at HB after bundle implementation and, Group 3 (n = 91) at HCM after bundle implementation. Demographic and clinical features, diagnosis of SSI, and clinical evolution of patients with SSI were analyzed. Results: There was similarity in the demographic and clinical features among groups, with mild increase of the surgical risk and time on mechanical ventilation in the Groups 2 and 3. There was decrease of SSI rate after bundle implementation: from 10.9% (Group 1) to 6.5% (Group 2), from 6.5% (Group 2) to 2.2% (Group 3), and from 10.9% (Group 1) to 2.2%. Improvement in the outcome of infection and reduction in the number of deaths were also observed. Conclusions: The implementation of bundle for the prevention of SSI combined with structural and physical differences of CardioPed ICU was effective in reducing of infection in the postoperative period.